The disruption of the protagonist’s routine and loneliness as a detonator of great short stories: - Atarama Rojas, Tomás (2017)
This article presents a study of the animated short films that won the Academy Award from 2011 to 2015, specifically focusing on how their protagonists move the story forward. The main characters in these five case studies are presented in a monotonous routine. This analysis has found that their lonely life is disrupted by an event out of the ordinary, which sets the story in motion. Along with this, the article illustrates that short films tend to develop a single plot and a single action with a single climax.